NILAI EDUKATIF DALAM SURAT AL-FATIHAH DAN PENGARUHNYA TERHADAP KARAKTER - Saputra, Edy (BASHA'IR: JURNAL STUDI AL-QUR'AN DAN TAFSIR, 2021)
This article examines the value of normative educatives in Surat Al-Fatihah and its effect on character. This study includes the category of literature research. The study method used is descriptive analytical. The primary data in this study is surat Al-Fatihah. While the secondary data as a support in this article comes from references related to the theme of discussion, especially the books of interpretation. The results of this study show that value is very important to instill in a person, because value is a reference and confidence in determining attitudes. Therefore, values greatly affect a person's character and behavior. Surat Al-Fatihah contains normative values in three aspects; (1) the value of i'tiqadiyah, (2) the value of Khuluqiyah, and (3) the value of amaliah (Sharia). However, this paper is limited to the study only on the value of akidah education (i'tiqadiyah) only and its effect on character. The reason, the creed is the foundation that becomes the foundation of sharia and morals. Shariah is the implementation of the creed. While morals are a reflection of the creed and sharia. So, the creed is a worldview or basic belief that becomes the main value in a person's life. In surat Al-Fatihah contains several values of the creed, namely faith and tawhid. And in surat Al-fatihah contains three types of tawhid in full, namely rububiyyah, uluhiyyah, and asmâ' wa shifat.